Preparation and in-vivo evaluation of cytochrome-C-containing liposomes - Katsai, O. G.; Ruban, O. A.; Krasnopolsky, Yu. M. (GOVI Verlag, Germany, 2017)
This study investigates the development of a method for obtaining cytochrome C-containing liposomes (LS-Cyt), and evaluates their stability and specific activity. LS-Cyt were intended for the therapy of ophthalmic diseases. LS-Cyt were prepared by high pressure homogenization technique and lyophilized to obtain freeze-dried LS-Cyt. It was proposed to use anionic phospholipid- dipalmitoylphosphatidylglycerol (DPPG-Na) and phosphatidylcholine (PC) in a nanoparticulate composition. Were investigated various concentrations of lactose and trehalose as cryoprotectants. Samples with a lactose concentration of 6% showed the best results in terms of the emulsion formation time, encapsulation and preservation of nanosize. The main technological parameters for the obtained freeze-dried LS-Cyt were encapsulation of no less than 95% of cytochrome C (Cyt C), particle size of 140-170 nm, pH of 6.85±0.1, osmolarity of 330±3 mOsmol/kg, a lysophosphatidylcholine content (LPC) of 0.65±0.05 % of the total of lipids. Stability of the freeze-dried LS-Cyt during storage was established. The freeze-dried LS-Cyt was kept for 1 year in a light protected place at the temperature of -15 °C. No changes in the composition of LS-Cyt samples were detected over the observation period. Preclinical in-vivo research was conducted, namely the evaluation of specific activity on the model of the penetrating corneal injury. It was established that use of LS-Cyt contributes to a more rapid process of tissue regeneration and reduction of the inflammatory response in comparison with a non-liposomal dosage form.